Neodymium-iron-boron magnet and preparation method thereof

The optimized microstructure and three-stage aging process in NdFeB magnets enhance coercive force and squareness by forming a high Co content RTM-Co phase, addressing the limitations of heavy rare earth diffusion and grain morphology issues, and reducing heavy rare earth usage.

CN119170367APending Publication Date: 2024-12-20NINGBO KONIT IND +4
View PDF 0 Cites 7 Cited by

Patent Information

Application Number
CN202411384796.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing neodymium iron boron (NdFeB) magnets face challenges in achieving high coercive force and squareness due to limited diffusion depth of heavy rare earth elements, which leads to reduced remanent magnetism and increased production costs, while adding elements like Ti and Zr for grain boundary diffusion results in adverse effects on magnetic properties and grain morphology.

Method used

A neodymium iron boron magnet with optimized microstructure, featuring a specific distribution of triangular region grain boundary phases and RTM-Co phases, along with a three-stage aging process, to enhance coercive force and squareness, and reduce heavy rare earth usage by incorporating elements like Ti and Zr.

Benefits of technology

The optimized microstructure and three-stage aging process improve the roundness and spheroidization of main phase grains, forming a high Co content RTM-Co phase, resulting in higher coercive force and squareness, while reducing the need for heavy rare earth elements.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119170367A_ABST
    Figure CN119170367A_ABST
Patent Text Reader

Abstract

The invention relates to a neodymium-iron-boron magnet which comprises main-phase crystal grains, a thin-layer crystal boundary phase and a triangular-area crystal boundary phase. Grain boundary phase distribution of a triangular region in the neodymium-iron-boron magnet meets the condition that S1 / S is greater than or equal to 0.057 and less than or equal to 0.073 The neodymium-iron-boron magnet comprises R, M, M1, Co, B and T; r is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; m is selected from one or more of Al, Cu and Ga; m1 is selected from one or more of Ti, Zr, Nb, W and V; t is selected from Fe and other impurity elements; the content of R in the neodymium-iron-boron magnet is 28-32 wt%, and the content of M1 is 0.4-1.0 wt%; the triangular grain boundary phase comprises an R-T-M-Co phase, and the content of Co in the R-T-M-Co phase is 6.2 to 10.4 at%. The neodymium-iron-boron magnet provided by the invention has the advantages that the main phase grain roundness is high, the area proportion of the thin layer grain boundary phase is reduced, the area proportion of the triangular region grain boundary phase is increased, the atomic percent of Co in the R-T-M-Co phase formed in the triangular region grain boundary phase is increased, and the magnet has relatively high coercive force and squareness.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of neodymium iron boron magnets, and particularly relates to a neodymium iron boron magnet and a preparation method thereof. Background Art

[0002] Sintered NdFeB permanent magnet materials have outstanding advantages such as high magnetic properties and high cost performance. They are currently the magnetic materials with the broadest application prospects. As the application scenarios of NdFeB permanent magnet materials become more and more demanding, the requirements for performance are also getting higher and higher. In order to improve the coercive force and enhance the heat resistance, the grain boundary diffusion process has been often used in recent years to diffuse heavy rare earth elements from the surface of the magnet to the inside of the magnet, so that the heavy rare earth elements are concentrated in the outer shell area of ​​the main phase grains, thereby improving the coercive force of the magnet and inhibiting the reduction of the remanent magnetism Br. However, due to the limited diffusion depth of heavy rare earth elements and the enrichment of heavy rare earth inside the main phase grains, the remanent magnetism of the magnet is reduced, and the Hcj is increased by a small margin, resulting in a low utilization efficiency of heavy rare earths. Not only does the production cost increase, but the performance improvement effect of the magnet will also decay rapidly.

[0003] In order to reduce the use of heavy rare earths, in the existing formulation system, elements such as Ti and Zr are often added to replace part of Dy, and high-melting-point precipitates such as borides are formed during the sintering process to hinder the abnormal growth of grains and improve the coercivity of magnets. However, when the addition amount of elements such as Ti and Zr is further increased (i.e., when M1 is higher than 0.4wt%), although the grain boundary Nd-rich phase can be continuously distributed in a thin layer between the grains, hindering the generation of coupling between the grains, its effect of achieving magnetic isolation is limited. While the coercivity is limitedly improved, it has an adverse effect on the squareness of the magnet; in addition, when the addition amount of elements such as Ti and Zr is further increased, the main phase grains in the magnet are not smooth enough and there are defects on the edges, which will also affect the increase in coercivity, resulting in the improvement of comprehensive magnetic properties being limited. Summary of the invention

[0004] The purpose of the present invention is to provide a neodymium iron boron magnet and a preparation method thereof. The microstructure of the neodymium iron boron magnet prepared by the method provided by the present invention is effectively optimized, the roundness of the main phase grains is high, the area proportion of the thin layer grain boundary phase is reduced, the area proportion of the triangular region grain boundary phase is increased, and the atomic percentage of Co in the RTM-Co phase in the triangular region grain boundary phase is increased, so that the neodymium iron boron magnet has higher coercive force and squareness.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a NdFeB magnet, wherein the NdFeB magnet comprises main phase grains, thin layer grain boundary phase and triangular region grain boundary phase; The triangular region grain boundary phase distribution in the NdFeB magnet satisfies the following formula (1): 0.057≤S1 / S≤0.073 Formula (1); Wherein, S1 / S represents the ratio of the area S1 of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area S of the cross section; The NdFeB magnet comprises R, M, M1, Co, B and T; R is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; M is selected from one or more of Al, Cu and Ga; M1 is selected from one or more of Ti, Zr, Nb, W and V; T is selected from Fe and other impurity elements; the content of R in the NdFeB magnet is 28-32wt%, and the content of M1 is 0.4-1.0wt%; The triangular grain boundary phase includes an RTM-Co phase, and the content of Co in the RTM-Co phase is 6.2-10.4 at %.

[0006] Optionally, in the NdFeB magnet, the content of R is 28-32wt%, the content of M1 is 0.4-1.0wt%, the content of Co is 0.4-2wt%, the content of Cu is 0.1-0.25wt%, the content of Ga is 0.1-0.25wt%, the content of Al is 0.05-1.2wt%, the content of B is 0.85-1.05wt%, and the balance is Fe and other impurity elements; Optionally, R does not contain Ce and Gd; Preferably, the content of Ti in M1 is 0-0.4wt%, and the content of Zr is 0.25-0.7wt%; Preferably, M1 contains at least one of Ti and Zr; when the content of Ti in M1 is 0, the content of Zr is greater than 0.3 wt %, and when the content of Zr in M1 is 0, the content of Ti is greater than 0.2 wt %.

[0007] Optionally, the content of R in the RTM-Co phase is 38-90 at %; Preferably, the content of Cu in the RTM-Co phase is 4-9.7 at%, and the content of Ga is 2.9-6 at%.

[0008] Optionally, the RTM-Co phase distribution within the grain boundary of the triangular region satisfies the following formula (2): 0.162≤S2 / S1≤0.18 Formula (2); Wherein, S2 / S1 represents the ratio of the area S2 of all RTM-Co phases in the triangular grain boundary phase in the cross section of the NdFeB magnet to the area S1 of all triangular grain boundary phases in the cross section.

[0009] Optionally, the triangular grain boundary phase also includes R6T 13 M1 phase, R6T within the triangular grain boundary phase 13 The M1 phase distribution satisfies 0.8≤S3 / S1≤0.815; Wherein, S3 / S1 represents all R6T in the cross section of the NdFeB magnet. 13 The ratio of the area of ​​the M1 phase to the area of ​​all triangular grain boundary phases in the cross section.

[0010] Optionally, the roundness of the main phase grains is 0.6-0.9, and the average grain size of the main phase grains is 3.5-4.5 μm.

[0011] The second aspect of the present invention provides a method for preparing a NdFeB magnet, wherein the method comprises: sequentially performing a molding process on a raw alloy powder to obtain a compact, and performing a sintering process and an aging process on the compact; Wherein, the aging treatment includes a first aging treatment, a second aging treatment and a third aging treatment; The temperature of the first aging treatment is 870-940°C, and the holding time is 0.5-4h; the temperature of the second aging treatment is 420-670°C, and the holding time is 1-10h; the temperature of the third aging treatment is 620-670°C, and the holding time is 1-10h; The raw alloy powder includes R, M, M1, Co, B and T, R is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; M is selected from one or more of Al, Cu and Ga; M1 is selected from one or more of Ti, Zr, Nb, W and V; T is selected from Fe and other impurity elements; the content of R in the NdFeB magnet is 28~32wt%, and the content of M1 is 0.4~1.0wt%.

[0012] Optionally, the temperature of the second aging treatment is 450-660°C, and the temperature of the third aging treatment is 630-670°C.

[0013] Optionally, in the raw alloy powder, the content of R is 28~32wt%, the content of M1 is 0.4~1.0wt%, the content of Co is 0.4~2wt%, the content of Cu is 0.1~0.25wt%, the content of Ga is 0.1~0.25wt%, the content of Al is 0.05~1.2wt%, the content of B is 0.85~1.05wt%, and the balance is Fe and other impurity elements; optionally, R does not contain Ce and Gd.

[0014] The third aspect of the present invention provides a neodymium iron boron magnet prepared by the method described in the second aspect of the present invention.

[0015] Through the above technical scheme, the present invention increases the addition amount of high melting point elements Ti, Zr, and Nb, and reasonably designs the remaining components, and cooperates with the addition of low melting point elements Al, Cu, and Ga, and performs three-stage specific temperature aging treatment on NdFeB compacts with high content of elements such as Ti, Zr, Nb, and W, which can avoid the adverse effects of high melting point elements such as high content of Ti, Zr, and Nb on the main phase grain morphology and magnet performance, and further optimize the microstructure of the magnet. The method disclosed in the present invention can effectively eliminate the main phase grain tips of the magnet, improve the roundness of the main phase grains, further spheroidize the main phase grains, effectively enhance the repair effect of the main phase grains, and increase the area proportion of the triangular region grain boundary phase. At the same time, the eliminated main phase grain tips participate in the intergranular reaction, and the area proportion of the thin layer grain boundary phase is reduced, and some low melting point metal elements in the thin layer grain boundary phase enter the intergranular reaction, so that the RTM-Co phase with a high Co content is formed in the triangular grain boundary phase, so that the NdFeB magnet has a higher coercive force and squareness. In addition, the magnet of the present invention contains a high content of M1 including elements such as Ti and Zr, which can replace part of heavy rare earth elements such as Dy and Tb, thereby reducing the use of heavy rare earth.

[0016] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] The accompanying drawings are used to provide a further understanding of the present invention and constitute a part of the specification. Together with the following specific embodiments, they are used to explain the present invention but do not constitute a limitation of the present invention. In the accompanying drawings: Figure 1 This is a SEM image of the magnet prepared in Example 1 of the present invention.

[0018] Figure 2 This is a SEM image of the magnet prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0019] The specific implementation of the present disclosure is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described herein is only used to illustrate and explain the present disclosure, and is not used to limit the present disclosure.

[0020] The first aspect of the present disclosure provides a neodymium iron boron magnet, wherein the neodymium iron boron magnet comprises a main phase grain, a thin layer grain boundary phase and a triangular region grain boundary phase; The triangular region grain boundary phase distribution in the NdFeB magnet satisfies the following formula (1): 0.057≤S1 / S≤0.073 Formula (1); Wherein, S1 / S represents the ratio of the area S1 of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area S of the cross section; The NdFeB magnet comprises R, M, M1, Co, B and T; R is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; M is selected from one or more of Al, Cu and Ga; M1 is selected from one or more of Ti, Zr, Nb, W and V; T is selected from Fe and other impurity elements; the content of R in the NdFeB magnet is 28-32wt%, and the content of M1 is 0.4-1.0wt%; The triangular grain boundary phase includes an RTM-Co phase, and the content of Co in the RTM-Co phase is 6.2-10.4 at %.

[0021] The microstructure of the NdFeB magnet provided by the present disclosure is effectively optimized, the tips of the main phase grains can be effectively eliminated, the roundness of the main phase grains can be improved, the main phase grains are further spheroidized, the repairing effect of the main phase grains is effectively enhanced, and the area ratio of the grain boundary phase in the triangular region is increased. At the same time, the tips of the eliminated main phase grains can participate in the intergranular reaction, and the area ratio of the thin layer grain boundary phase is reduced, and some low-melting-point metal elements in the thin layer grain boundary phase enter the intergranular reaction to participate in the reaction, so that the RTM-Co phase is formed in the triangular grain boundary phase, and the atomic percentage of Co in the RTM-Co phase is increased, so that the NdFeB magnet has a higher coercive force and squareness. In addition, the present invention adds elements such as Ti and Zr to replace part of Dy, thereby hindering the abnormal growth of grains during the sintering process and effectively improving the coercive force of the magnet. When the addition amount of elements such as Ti and Zr is further increased (that is, when M1 is higher than 0.4wt%), the roundness of the main phase grains in the magnet is further improved, and an RTM-Co phase with a high Co content is formed in the grain boundary phase, which can have both high coercive force and squareness.

[0022] In the present disclosure, the S1 / S value of the NdFeB magnet can be represented by the average result of the S1 / S values ​​of multiple cross-sections of the magnet, that is, multiple different cross-sections of the magnet can be randomly selected to measure the S1 / S values ​​respectively, and the average value of the S1 / S values ​​of the multiple different cross-sections represents the S1 / S value of the magnet.

[0023] For example, the S1 / S value of the NdFeB magnet can be determined by the following method: perform a scanning electron microscope test on any five or more sections of the magnet, count the areas of all triangular grain boundary phases in each section, calculate the S1 / S value of each section, and then find the average value of the S1 / S values ​​of all sections as the S1 / S value of the NdFeB magnet; the size of the observation area is, for example, 40μm×40μm and 75μm×75μm; the magnification is 2000~5000 times.

[0024] In a specific embodiment, S1 / S is 0.058-0.072. For example, S1 / S is 0.058, 0.060, 0.062, 0.064, 0.066, 0.068, 0.070, 0.072 or any value in the range of any two thereof.

[0025] In a specific embodiment, in the NdFeB magnet, the content of R is 28~32wt%, the content of M1 is 0.4~1.0wt%, the content of Co is 0.4~2wt%, M contains Cu, Ga and Al, the content of Cu is 0.1~0.25wt%, the content of Ga is 0.1~0.25wt%, the content of Al is 0.05~1.2wt%, the content of B is 0.85~1.05wt%, and the balance is Fe and other impurity elements; optionally, R does not contain Ce and does not contain Gd.

[0026] Exemplarily, the content of R in the NdFeB magnet is 28wt%, 28.5wt%, 29wt%, 29.5wt%, 30wt%, 30.5wt%, 31wt%, 31.5wt%, 32wt% or a range consisting of any two thereof.

[0027] Illustratively, the content of M1 in the NdFeB magnet is 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1.0 wt%, or any value in a range consisting of any two thereof.

[0028] In a specific embodiment, the content of Ti in M1 is 0-0.4wt%, and the content of Zr is 0.25-0.7wt%; In a specific embodiment, M1 includes at least one of Ti and Zr, and optionally includes one or more of Nb, W and V.

[0029] In a further embodiment, when the Ti content in M1 is 0, the Zr content is greater than 0.3 wt %.

[0030] In a further embodiment, when the Zr content in M1 is 0, the Ti content is greater than 0.2 wt %.

[0031] In a specific embodiment, the content of Co in the RTM-Co phase is 6.3-10.3 at%. For example, the content of Co in the RTM-Co phase is 6.3 at%, 6.5 at%, 7 at%, 7.5 at%, 8 at%, 8.5 at%, 9 at%, 9.5 at%, 10 at%, 10.3 at%, or any value in the range of any two thereof.

[0032] In a specific embodiment, the content of R in the RTM-Co phase is 38-90 at%. For example, the content of R in the RTM-Co phase is 38 at%, 40 at%, 45 at%, 50 at%, 55 at%, 60 at%, 65 at%, 70 at%, 75 at%, 80 at%, 85 at%, 90 at%, or any value in the range of any two thereof.

[0033] In a preferred embodiment, the content of Cu in the RTM-Co phase is 4-9.7at%, and the content of Ga is 2.9-6at%. For example, the content of Cu in the RTM-Co phase is 4at%, 4.5at%, 5at%, 5.5at%, 6at%, 6.5at%, 7at%, 7.5at%, 8at%, 8.5at%, 9at%, 9.5at%, 9.7at% or any two thereof; the content of Ga in the RTM-Co phase is 2.9at%, 3.2at%, 3.5at%, 4at%, 4.5at%, 5at%, 5.5at%, 6at% or any value in the range of any two thereof. In the above embodiment, the RTM-Co phase with high content of Cu and Ga helps to hinder the propagation of the demagnetization field between grains, further effectively improves the microstructural uniformity of the magnet, realizes the fine structure control of the magnet grain boundary, enhances the demagnetization coupling effect, repairs the surface defects of the main phase grains, and makes the magnet have high coercive force and excellent magnetic properties.

[0034] In a specific embodiment, the distribution of the RTM-Co phase in the triangular region grain boundary satisfies the following formula (2), 0.162≤S2 / S1≤0.18 Formula (2); wherein S2 / S1 represents the ratio of the area S2 of all RTM-Co phases in the triangular region grain boundary phase in the cross section of the NdFeB magnet to the area S1 of all triangular grain boundary phases in the cross section. In the above embodiment, the Co-enriched RTM-Co phase enables the NdFeB magnet to have higher coercivity and squareness. Exemplarily, S2 / S1 is 0.162, 0.164, 0.166, 0.168, 0.17, 0.172, 0.174, 0.176, 0.178, 0.18 or any value in the range of any two of them.

[0035] In the present disclosure, the S2 / S1 value of the NdFeB magnet can be represented by the average result of the S2 / S1 values ​​of multiple cross-sections of the magnet, that is, multiple different cross-sections of the magnet can be randomly selected to measure the S2 / S1 values ​​respectively, and the average value of the S2 / S1 values ​​of the multiple different cross-sections represents the S2 / S1 value of the magnet.

[0036] For example, the S2 / S1 value of the NdFeB magnet can be determined by the following method: perform a scanning electron microscope test on any five or more sections of the magnet, count the areas of all RTM-Co phases within the triangular grain boundaries of each section, calculate the S2 / S1 value of each section, and then find the average value of the S2 / S1 values ​​of all sections as the S2 / S1 value of the NdFeB magnet; the size of the observation area is, for example, 40μm×40μm and 75μm×75μm; the magnification is 2000~5000 times.

[0037] In a specific embodiment, the triangular grain boundary phase also includes R6T 13 M1 phase, R6T within the triangular grain boundary phase 13 The M1 phase distribution satisfies 0.8≤S3 / S1≤0.815; wherein S3 / S1 represents all R6T in the NdFeB magnet. 13 The ratio of the area of ​​the M1 phase to the area of ​​all triangular grain boundary phases in the cross section.

[0038] According to the present disclosure, the main phase grains of the magnet have a high roundness, which helps to further increase the area ratio of the grain boundary phase in the triangular region, promote the formation of the RTM-Co phase, and reduce the area ratio of the thin layer grain boundary phase. In a specific embodiment, the roundness of the main phase grains is 0.6~0.9, preferably 0.65~0.9. For example, the roundness of the main phase grains can be any value in the range of 0.6, 0.65, 0.7, 0.75, 0.8, 0.85, 0.9 or any two of them.

[0039] In the present disclosure, the roundness of the main phase grains is calculated using the following formula (3): roundness = 4πS4 / C 2 , formula (3); where S4 is the cross-sectional area of ​​the main phase grain, and C is the circumference of the main phase grain.

[0040] In the present disclosure, the roundness of the main phase grains can be represented by the average result of the roundness of the main phase grains in multiple cross-sections of the magnet, that is, multiple different cross-sections of the magnet can be randomly selected to measure the roundness of the main phase grains in the cross-sections respectively, and the average value of the roundness of the main phase grains in the multiple different cross-sections represents the roundness of the main phase grains of the magnet.

[0041] In a specific embodiment, the average grain size of the main phase grains is 3.5-4.5 μm. For example, the average grain size of the main phase grains can be 3.5 μm, 3.7 μm, 3.9 μm, 4.1 μm, 4.3 μm, 4.5 μm, or any value in the range of any two thereof.

[0042] In the present disclosure, the average grain size refers to the average value of the equivalent circle diameter calculated from the cross-sectional area of ​​the main phase grains.

[0043] A second aspect of the present disclosure provides a method for preparing a neodymium iron boron magnet, wherein the method comprises: sequentially performing a molding process on a raw alloy powder to obtain a compact, and performing a sintering process and an aging process on the compact; Wherein, the aging treatment includes a first aging treatment, a second aging treatment and a third aging treatment; The temperature of the first aging treatment is 870-940°C, and the holding time is 0.5-4h; the temperature of the second aging treatment is 420-670°C, and the holding time is 1-10h; the temperature of the third aging treatment is 620-670°C, and the holding time is 1-10h; The raw alloy powder includes R, M, M1, Co, B and T, R is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; M is selected from one or more of Al, Cu and Ga; M1 is selected from one or more of Ti, Zr, Nb, W and V; T is selected from Fe and other impurity elements; the content of R in the NdFeB magnet is 28~32wt%, and the content of M1 is 0.4~1.0wt%.

[0044] The present invention discloses a three-stage specific temperature aging treatment for NdFeB compacts with high content of high melting point elements such as Ti, Zr, and Nb, which can avoid the adverse effects of high melting point elements such as high content of Ti, Zr, and Nb on the main phase grain morphology and magnet performance, further optimize the microstructure of the magnet, and achieve fine structure control of the magnet grain boundary. The method disclosed in the present invention can effectively eliminate the tips of the main phase grains of the magnet, improve the roundness of the main phase grains, further spheroidize the main phase grains, effectively enhance the repair effect of the main phase grains, and increase the area ratio of the triangular region grain boundary phase. At the same time, the tips of the eliminated main phase grains can participate in the intergranular reaction, and the area ratio of the thin layer grain boundary phase is reduced. Some low melting point metal elements in the thin layer grain boundary phase enter the intergranular reaction, so that the RTM-Co phase with a high content of Co is formed in the triangular grain boundary phase, so that the NdFeB magnet has a higher coercive force and squareness. In addition, the magnet disclosed in the present invention contains elements such as Ti and Zr, and has a high content of M1, which can replace part of Dy and Tb and reduce the use of heavy rare earths.

[0045] For example, the temperature of the first aging treatment can be 870°C, 875°C, 880°C, 885°C, 890°C, 895°C, 900°C, 905°C, 910°C, 915°C, 920°C, 925°C, 930°C, 935°C, 940°C, or any value in the range consisting of any two thereof.

[0046] In a preferred embodiment, the temperature of the second aging treatment is 450-660°C. For example, the temperature of the second aging treatment can be 450°C, 455°C, 460°C, 465°C, 470°C, 475°C, 480°C, 485°C, 490°C, 495°C, 500°C, 505°C, 510°C, 515°C, 520°C, 525°C, 530°C, 535°C, 540°C, ℃, 545℃, 550℃, 555℃, 560℃, 565℃, 570℃, 575℃, 580℃, 585℃, 590℃, 595℃, 600℃, 605℃, 610℃, 615℃, 620℃, 625℃, 630℃, 635℃, 640℃, 645℃, 650℃, 655℃, 660℃ or any value in the range consisting of any two of them.

[0047] In a preferred embodiment, the temperature of the third aging treatment is 630-670° C. For example, the temperature of the third aging treatment can be 630° C., 635° C., 640° C., 645° C., 650° C., 655° C., 660° C., 665° C., 670° C., or any value in the range consisting of any two of them.

[0048] In the above embodiment, the preferred temperatures of the second aging treatment and the third aging treatment can further avoid the adverse effects of high-melting-point elements such as high contents of Ti, Zr, Nb, etc. on the main phase grain morphology and magnet performance, further optimize the microstructure of the magnet, and enable the prepared magnet to have higher coercive force and squareness.

[0049] In a specific embodiment, in the raw alloy powder, the content of R is 28~32wt%, the content of M1 is 0.4~1.0wt%, the content of Co is 0.4~2wt%, the content of Cu is 0.1~0.25wt%, the content of Ga is 0.1~0.25wt%, the content of Al is 0.05~1.2wt%, the content of B is 0.85~1.05wt%, and the balance is Fe and other impurity elements; optionally, R does not contain Ce and Gd.

[0050] In a specific embodiment, the method further comprises: preparing a raw alloy sheet by a rapid solidification process, performing hydrogen crushing treatment and air flow mill fine pulverization treatment on the raw alloy sheet to obtain the raw alloy powder; the D50 particle size of the raw alloy powder is 2 to 5 μm. For example, the D50 particle size of the raw alloy powder can be any value in the range of 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm, 5 μm or any value in the range of any two of them.

[0051] In a specific embodiment, the molding process is an orientation molding process, and the orientation molding process is performed under the condition that the orientation magnetic induction intensity is 1.8 to 2.5 T. For example, the orientation magnetic induction intensity can be any value in the range of 1.8 T, 1.9 T, 2.0 T, 2.1 T, 2.2 T, 2.3 T, 2.4 T, 2.5 T or any two thereof.

[0052] In a specific embodiment, the sintering temperature is 1030-1120°C, and the holding time is 1-10h. For example, the sintering temperature can be 1030°C, 1040°C, 1050°C, 1060°C, 1070°C, 1080°C, 1090°C, 1100°C, 1110°C, 1120°C, or any value in the range of any two of them.

[0053] A third aspect of the present disclosure provides a neodymium iron boron magnet prepared by the method described in the second aspect of the present disclosure.

[0054] The NdFeB magnet prepared by the method provided by the present disclosure has higher coercive force and squareness.

[0055] The present invention is further illustrated by the following examples, but the present invention is not limited thereto.

[0056] Example 1 S1. Prepare raw alloy powder by the following steps: (1) Raw alloy powders are prepared in wt% by weight, wherein R is Pr and Nd, M includes Al, Cu and Ga, and M1 includes Zr; wherein R is 30wt%, M1 (Zr) is 0.5wt%, Ga is 0.2wt%, Cu is 0.1wt%, Co is 0.9wt%, Al is 0.5wt%, B is 0.92wt%, and the remainder is Fe; the prepared raw alloy powders are cast into raw alloy quick-setting sheets by a quick-setting process; the raw alloy quick-setting sheets are subjected to hydrogen crushing and micro-grinding respectively to obtain raw alloy powders; wherein the hydrogen absorption pressure of hydrogen crushing is 0.3MPa, the dehydrogenation temperature is 560°C, the micro-grinding is carried out in a jet mill, the grinding pressure of the jet mill is 0.68MPa, and the average particle size D50 of the raw alloy powder is 4μm; S2. Using the obtained raw alloy powder to prepare NdFeB magnets: The raw alloy powder is subjected to molding, sintering and aging treatment to obtain a NdFeB magnet 1, denoted as CT-1. The molding treatment is an oriented molding treatment, which is carried out under the protection of N2 gas and under the condition of an oriented magnetic induction intensity of 2T; the sintering treatment is carried out in a vacuum or inert atmosphere, the sintering temperature is 1080°C, the sintering time is 8h, and the gas quenching is to room temperature; the aging treatment includes a first aging treatment, a second aging treatment and a third aging treatment, the first aging treatment temperature is 940°C, the insulation time is 1h, the second aging temperature is 480°C, the insulation time is 8h, and the third aging treatment temperature is 640°C, the insulation time is 5h.

[0057] The prepared NdFeB magnet 1 was subjected to microstructural testing. The test results showed that the NdFeB magnet CT-1 consisted of main phase grains and grain boundary phases. The grain boundary phases included thin-layer grain boundary phases and triangular grain boundary phases. The triangular grain boundary phases contained RTM-Co phase (high-brightness grain boundary phase) and R6T 13 M1 phase (gray grain boundary phase). The thin layer grain boundary phase refers to the grain boundary phase formed between two adjacent main phase grains; the triangular area grain boundary phase refers to the grain boundary phase surrounded by three or more main phase grains.

[0058] The distribution of the triangular grain boundary phase and the RTM-Co phase in the NdFeB magnet prepared in Example 1 was statistically calculated using image analysis software (image pro plus), and S1 / S was 0.072, S2 / S1 was 0.165, and S3 / S1 was 0.802; the results are as follows: Figure 1 As shown, it indicates that the area of ​​the grain boundary phase in the triangular region of the magnet accounts for a higher proportion, and the main phase grains have a higher roundness, which makes the NdFeB magnet have a higher coercive force and squareness.

[0059] Example 2 The method of Example 1 was adopted, except that the temperature of the second aging treatment was 670° C., to obtain a NdFeB magnet 2, which was designated as CT-2.

[0060] Example 3 The method of Example 1 was adopted, except that the temperature of the second aging treatment was 420° C. and the temperature of the third aging treatment was 670° C., to obtain a NdFeB magnet 3, which was recorded as CT-3.

[0061] Example 4 The method of Example 1 was adopted, except that the temperature of the second aging treatment was 630° C., to obtain a NdFeB magnet 4, which was recorded as CT-4.

[0062] Example 5 Referring to the preparation method in Example 1, the difference from Example 1 is that in step S1, (1) Raw alloy powders were prepared in wt% by mass, wherein R was 28.5wt%, R was Pr and Nd, M1 was 1.0wt%, M1 included 0.6wt% Zr and 0.4wt% Ti; Ga was 0.1wt%, Cu was 0.15wt%, Co was 2wt%, Al was 1wt%, B was 0.94wt%, and the remainder was Fe. NdFeB magnet 5 was obtained, which was recorded as CT-5.

[0063] Example 6 Referring to the preparation method in Example 1, the difference from Example 1 is that in step S1, (1) Raw material alloy powders were prepared in wt% by mass, wherein R was 30wt%, R was Pr and Nd, M1 was 0.4wt%, M1 included 0.3wt% Ti and 0.1wt% Zr; Ga was 0.2wt%, Cu was 0.2wt%, Co was 0.6wt%, Al was 1wt%, B was 0.88wt%, and the remainder was Fe. NdFeB magnet 6 was obtained, which was recorded as CT-6.

[0064] Comparative Example 1 Referring to the preparation method in Example 1, the difference from Example 1 is that in step S2, the aging treatment includes a first aging treatment and a second aging treatment, the temperature of the first aging treatment is 890°C, and the holding time is 4 hours; the temperature of the second aging treatment is 500°C, and the holding time is 8 hours, and a neodymium iron boron magnet is obtained, which is recorded as DCT-1.

[0065] Comparative Example 2 Referring to the preparation method in Example 1, the difference from Example 1 is that in step S2, the temperature of the second aging treatment is 680° C., and the holding time is 8 hours, to obtain a NdFeB magnet, which is recorded as DCT-2.

[0066] Comparative Example 3 Referring to the preparation method in Example 1, the difference from Example 1 is that in step S2, the temperature of the third aging treatment is 600° C., and the holding time is 8 hours, to obtain a neodymium iron boron magnet, which is recorded as DCT-3.

[0067] Comparative Example 4 Referring to the preparation method in Example 1, the difference from Example 1 is that in step S1, (1) Raw alloy powders are prepared in wt% by weight, wherein M1 is 0.3 wt% and M1 includes 0.1 wt% Zr and 0.2 wt% Ti. A NdFeB magnet is obtained, which is denoted as DCT-4.

[0068] Test Case The NdFeB magnets prepared in Examples 1 to 6 and Comparative Examples 1 to 4 were selected and EPMA scanning was used to measure the atomic percentage of each element in the grain boundary phase. The results are listed in Tables 1 and 2.

[0069] The average particle size of the raw alloy powder is measured using a particle size analyzer.

[0070] After the magnet of Example 1 was sampled, a cross-sectional image was taken using a scanning electron microscope. The obtained SEM image is as follows: Figure 1 As shown, the observation plane is perpendicular to the orientation direction of the magnet. The grain boundary phase in the triangular region of the magnet in Example 1 includes RTM-Co phase (highlighted white) and R6T 13 M1 phase (gray), RTM-Co phase and R6T 13 The M1 phase can be distinguished based on the electron backscattered image. The contrast of the backscattered electron image of the RTM-Co phase is slightly higher than that of the R6T phase. 13 M1 phase.

[0071] The size and roundness of the main phase grains were statistically analyzed using image-pro plus image analysis software: more than 5 random sections of the magnet were randomly selected for analysis, wherein more than 5 40μm×40μm areas were randomly selected from each section (the total number of main phase grains in the field of view was more than 200), and the average size and roundness of all complete main phase grains in each area in each section were measured, and the average value of the average size and the average value of the roundness of the main phase grains in all areas were calculated as the average size and roundness of the main phase grains of the magnet.

[0072] The triangular grain boundary phase of the magnet, the RTM-Co phase in the triangular grain boundary phase and the R6T 13 The distribution of M1 phase can be statistically analyzed by using image-pro plus image analysis software: randomly select more than 5 arbitrary sections in the magnet for analysis, wherein more than 5 40μm×40μm areas are randomly selected from each section (the total number of main phase grains in the field of view is more than 200), and the area S1 of the grain boundary phase in the triangular zone, the area S2 of the RTM-Co phase, and the area S6T of the RTM-Co phase in each area of ​​each section are measured respectively. 13 The area S3 of the M1 phase and the total area S of each area are calculated, the S1 / S value of each area is calculated and the average value is taken as the S1 / S value of the section, and then the average value of the S1 / S values ​​of all sections is calculated as the S1 / S value of the magnet. Similarly, the S2 / S1 value and S3 / S1 value of the magnet are obtained. The results are listed in Table 2.

[0073] The magnetic properties of the NdFeB magnets of Examples 1 to 6 and Comparative Examples 1 to 4 were tested using a BH plotter. The results are listed in Table 3.

[0074] Table 1

[0075] Table 2

[0076] Table 3

[0077] According to Tables 1 to 3, it can be seen that the present disclosure increases the addition amount of high melting point elements Ti, Zr, and Nb, while reasonably designing the remaining components, and cooperates with the addition of low melting point elements Al, Cu, and Ga, and performs three-stage specific temperature aging treatment on the NdFeB compact with high content of elements such as Ti, Zr, Nb, and W, which can avoid the adverse effects of high melting point elements such as high content of Ti, Zr, and Nb on the main phase grain morphology and magnet performance, further optimize the microstructure of the magnet, and realize the fine structure control of the magnet grain boundary. The method disclosed in the present disclosure can effectively eliminate the main phase grain tips of the magnet, improve the roundness of the main phase grains, further spheroidize the main phase grains, effectively enhance the repair effect of the main phase grains, and make the area of ​​the triangular region grain boundary phase in the magnets of Examples 1 to 6 account for a high proportion. At the same time, the tips of the eliminated main phase grains participate in the intergranular reaction, which reduces the area ratio of the thin layer grain boundary phase, and some low melting point metal elements in the thin layer grain boundary phase enter the intergranular phase to participate in the reaction, so that the RTM-Co phase with a high Co content is formed in the triangular grain boundary phase, so that the coercive force and squareness of the NdFeB magnets prepared in Examples 1 to 6 are higher than those in Comparative Examples 1 to 4. In addition, the M1 content of elements such as Ti and Zr in the magnet disclosed in the present invention is relatively high, which can replace some heavy rare earth elements such as Dy and Tb, thereby reducing the use of heavy rare earth.

[0078] By comparing Example 2 with Example 1 and Example 4, it can be seen that controlling the temperature of the second aging treatment within the preferred range of the present application can further optimize the microstructure of the magnet, further improve the roundness of the main phase grains, further spheroidize the main phase grains, effectively enhance the repair effect of the main phase grains, and further improve the coercive force and squareness of the prepared NdFeB magnet.

[0079] By comparing Comparative Example 1 with Example 1, it can be seen that since only two stages of aging treatment were performed on the NdFeB compact in Comparative Example 1, the high content of high melting point elements such as Ti, Zr, and Nb would have an adverse effect on the main phase grain morphology and magnet performance, and the main phase grain tips of the magnet could not be effectively eliminated. Figure 2As shown, the roundness of the main phase grains is low, the area proportion of the triangular grain boundary phase in the magnet is lower than that of Examples 1 to 6, the area proportion of the thin layer grain boundary phase is increased, and some low-melting-point metal elements in the thin layer grain boundary phase cannot enter the intergranular space to participate in the reaction, so that the Co content in the RTM-Co phase formed in the triangular grain boundary phase is low, which reduces the coercive force of the magnet prepared in Comparative Example 1 and significantly reduces the squareness.

[0080] By comparing Comparative Examples 2 and 3 with Example 1, it can be seen that when the temperature of the second aging treatment and the temperature of the third aging treatment are not within the specified range of the present application, the adverse effects of high-melting-point elements such as high content of Ti, Zr, Nb on the main phase grain morphology and magnet performance cannot be effectively controlled, the main phase grain tips of the magnet cannot be effectively eliminated, the roundness of the main phase grains is low, the area proportion of the triangular region grain boundary phase in the magnet is lower than that of Examples 1 to 6, the area proportion of the thin layer grain boundary phase is increased, some low-melting-point metal elements in the thin layer grain boundary phase cannot enter the intergranular space to participate in the reaction, so that the Co content in the RTM-Co phase formed in the triangular grain boundary phase is low, so that the coercive force of the magnet prepared in Comparative Example 1 is reduced, and the squareness is significantly reduced.

[0081] By comparing Comparative Example 4 with Example 1, it can be seen that when M is less than 0.4, the coercive force and squareness of the magnet prepared by this process are not significantly improved.

[0082] The preferred embodiments of the present invention are described in detail above in conjunction with the accompanying drawings. However, the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, a variety of simple modifications can be made to the technical solution of the present invention, and these simple modifications all belong to the protection scope of the present invention.

[0083] It should also be noted that the various specific technical features described in the above specific embodiments can be combined in any suitable manner without contradiction. In order to avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0084] In addition, various embodiments of the present invention may be arbitrarily combined, and as long as they do not violate the concept of the present invention, they should also be regarded as the contents disclosed by the present invention.

Claims

1. A neodymium iron boron magnet, wherein: The NdFeB magnet comprises main phase grains, thin layer grain boundary phase and triangular region grain boundary phase; The triangular region grain boundary phase distribution in the NdFeB magnet satisfies the following formula (1): 0.057≤S1 / S≤0.073 Formula (1); Wherein, S1 / S represents the ratio of the area S1 of all triangular grain boundary phases in the cross section of the NdFeB magnet to the total area S of the cross section; The NdFeB magnet comprises R, M, M1, Co, B and T; R is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; M is selected from one or more of Al, Cu and Ga; M1 is selected from one or more of Ti, Zr, Nb, W and V; T is selected from Fe and other impurity elements; the content of R in the NdFeB magnet is 28-32wt%, and the content of M1 is 0.4-1.0wt%; The triangular grain boundary phase includes an RTM-Co phase, and the content of Co in the RTM-Co phase is 6.2-10.4 at %.

2. The NdFeB magnet according to claim 1, wherein: In the NdFeB magnet, the content of R is 28-32wt%, the content of M1 is 0.4-1.0wt%, the content of Co is 0.4-2wt%, the content of Cu is 0.1-0.25wt%, the content of Ga is 0.1-0.25wt%, the content of Al is 0.05-1.2wt%, the content of B is 0.85-1.05wt%, and the balance is Fe and other impurity elements; optionally, R does not contain Ce and Gd; Preferably, the content of Ti in M1 is 0-0.4wt%, and the content of Zr is 0.25-0.7wt%; Preferably, M1 contains at least one of Ti and Zr; when the content of Ti in M1 is 0, the content of Zr is greater than 0.3 wt %, and when the content of Zr in M1 is 0, the content of Ti is greater than 0.2 wt %.

3. The NdFeB magnet according to claim 1, wherein: The content of R in the RTM-Co phase is 38-90 at %; Preferably, the content of Cu in the RTM-Co phase is 4-9.7 at%, and the content of Ga is 2.9-6 at%.

4. The NdFeB magnet according to claim 1, wherein: The RTM-Co phase distribution within the triangular region grain boundary satisfies the following formula (2): 0.162≤S2 / S1≤0.18 Formula (2); Wherein, S2 / S1 represents the ratio of the area S2 of all RTM-Co phases in the triangular grain boundary phase in the cross section of the NdFeB magnet to the area S1 of all triangular grain boundary phases in the cross section.

5. The NdFeB magnet according to claim 1, wherein: The triangular grain boundary phase also includes R6T 13 M1 phase, R6T within the triangular grain boundary phase 13 The M1 phase distribution satisfies 0.8≤S3 / S1≤0.815; Wherein, S3 / S1 represents all R6T in the cross section of the NdFeB magnet. 13 The ratio of the area of ​​the M1 phase to the area of ​​all triangular grain boundary phases in the cross section.

6. The NdFeB magnet according to claim 1, wherein: The roundness of the main phase grains is 0.6-0.9, and the average grain size of the main phase grains is 3.5-4.5 μm.

7. A method for preparing a neodymium iron boron magnet, wherein: The method comprises: performing molding treatment on raw alloy powder in sequence to obtain a compact, and performing sintering treatment and aging treatment on the compact; Wherein, the aging treatment includes a first aging treatment, a second aging treatment and a third aging treatment; The temperature of the first aging treatment is 870-940°C, and the holding time is 0.5-4h; the temperature of the second aging treatment is 420-670°C, and the holding time is 1-10h; the temperature of the third aging treatment is 620-670°C, and the holding time is 1-10h; The raw alloy powder includes R, M, M1, Co, B and T, R is selected from one or more of Nd, Pr, Ho, Ce, Gd, Dy and Tb; M is selected from one or more of Al, Cu and Ga; M1 is selected from one or more of Ti, Zr, Nb, W and V; T is selected from Fe and other impurity elements; the content of R in the NdFeB magnet is 28~32wt%, and the content of M1 is 0.4~1.0wt%.

8. The method according to claim 8, wherein: The temperature of the second aging treatment is 450-660°C, and the temperature of the third aging treatment is 630-670°C.

9. The method according to claim 8, wherein: In the raw alloy powder, the content of R is 28~32wt%, the content of M1 is 0.4~1.0wt%, the content of Co is 0.4~2wt%, the content of Cu is 0.1~0.25wt%, the content of Ga is 0.1~0.25wt%, the content of Al is 0.05~1.2wt%, the content of B is 0.85~1.05wt%, and the balance is Fe and other impurity elements; optionally, R does not contain Ce and Gd.

10. A neodymium iron boron magnet prepared by the method described in any one of claims 7 to 9.

Citation Information

Cited By

  • Heavy-rare-earth-free high-residual-magnetism high-coercive-force magnet and preparation method thereof

    CN119763966A

  • A heavy rare earth-free magnet with high remanence and high coercivity and its preparation method

    CN119763966B

  • High-residual-magnetism high-coercive-force magnet and preparation method thereof

    CN119763967A

  • A high remanence high coercivity magnet and method of making same

    CN119763967B

  • Low-cost magnet and preparation method thereof

    CN119763968A